Association of serum adiponectin levels with metabolic syndrome risk factors in Malay adults - Isa, Nur Firdaus; Mohd Zainuddin, Laila Ruwaida; Wan Muda, Wan Manan; Jan Mohamed, Hamid Jan (World Public Health Nutrition, 2017)
This study aimed to investigate the relationship between serum adiponectin and metabolic syndrome in adults living in rural Malaysia Methods: A total of 299 Malay adults (men=124; women = 175) with a mean age 48.8 (11.7) years were recruited. Measurements for waist circumference and blood pressure were taken before drawing an overnight fasting blood samples. Biochemical tests for triglycerides, HDL cholesterol, glucose and serum adiponectin concentration were measured. Results: Our results show that the adiponectin level in the subjects with metabolic syndrome was significantly lower than those without metabolic syndrome (p < 0.05). Among the metabolic syndrome risk factors, adiponectin level was significantly associated with hypertriglyceridemia and reduced HDL cholesterol (p < 0.001). Conclusion: The outcome from this study which highlights the association of hypoadiponectinemia with risk factors of metabolic syndrome in Malay adults, suggests that the reduced level of adiponectin may play a pivotal role in the development of metabolic syndrome in this ethnic group.